Nonlinear Dynamics for Local Fractional Burgers Equation Arising in Fractal Flow - Yang, Xiao-Jun (2015)
The local fractional Burgers’ equation (LFBE) is investigated from the point of view of local fractional conservation laws envisaging a nonlinear local fractional transport equation with a linear non-differentiable diffusion term. The local fractional derivative transformations and the LFBE conversion to a linear local fractional diffusion equation are analyzed.